Geochemistry and geochronology of intermediate volcanic rocks from the Compostela area, Nayarit, Mexico: Implications for petrogenesis and tectonic setting. (14th June 2021) - Ruiz‐Mendoza, Vivian; Verma, Sanjeet K.; Torres‐Sánchez, Darío; Barry, Tiffany L.; Moreno, Juan A.; Torres‐Hernández, José Ramón
Abstract : The Compostela area is located in the western Trans‐Mexican Volcanic Belt, which consists of volcanic rocks that produced during the Pliocene to Recent volcanism. In this paper, we present petrography, whole‐rock major‐ and trace‐element concentrations, Ar–Ar ages, and Sr–Nd isotopic data of volcanic rocks from the Compostela area in the south of the city of Tepic, Nayarit, Mexico. These volcanic rocks are of intermediate composition and belong to the transitional series: basaltic trachyandesites [52.72–53.94 wt% SiO2 ; 0.69–2.53 wt% MgO] and subalkaline series: low‐Si [55.11–60.94 wt% SiO2 ; 0.79–2.74 wt% MgO] and high‐Si [61.60–62.71 wt% SiO2; 0.36–0.80 wt% MgO] andesites. The 40 Ar/ 39 Ar dating of two basaltic trachyandesites yields plateau ages of 1.05 ± 0.15 Ma and 1.07 ± 0.17 Ma and the andesites yielded a plateau age of 2.42 ± 0.36 Ma. These results indicate that the studied rocks were formed during the Pleistocene in two discrete episodes. The basaltic trachyandesites show enriched light rare earth elements patterns relative to high rare earth elements [(La/Yb)N  = 5.81–8.07] with negligible Eu anomalies. The andesites display enriched large‐ion lithophile elements (Ba, K) with anomalies of Nb (Th/Ce) and Ti in the three groups identified in the subalkaline series. The basaltic trachyandesites appear in a tight cluster of initial 87 Sr/ 86 Sr ratios (0.703519–0.703882) as compared to the basaltic andesite 87 Sr/ 86 Sr (0.704073) and positive ɛ Nd( t ) values of +5.6 to +3.4, respectively, indicating that the basaltic trachyandesites were derived from intermediate magmas from a shallow mantle source. Geochemical modelling reveals that both basaltic trachyandesite and andesite rocks were derived by a process of crystal fractionation accompanied by assimilation of crustal rocks at the lower or middle level. Geochemical ratios and multidimensional discrimination diagrams, combined with the cross‐section of the subduction zone indicates that basaltic trachyandesites were generated from a rift and/or Ocean Island Basalt‐type source, whereas andesites were generated from a slab‐derived source in a subduction environment. Abstract : Graphical abstract presents a diagrammatic illustration of the subduction zone of the Rivera plate is mostly below the Jalisco Block outward of the western sector of TMVB. This observation supports the argument that the young and small Rivera plate has torn and the remaining shallow steepening slab is rolling back trenchward, and that between the Rivera and Cocos slabs exists a gap that increases in size at depth and the Rivera plate subducts more steeply than the Cocos plate. This gap allows magma from the deep mantle (asthenosphere), below the subducted Rivera slab, to rise through the mantle wedge resulting in OIB‐like basalts (transitional series). Over the remaining shallow slab, subduction related magmas with andesitic composition (sub‐alkaline series) develop.